Sense of presence and sense of place in perceiving a 3D geovisualization for communication in urban planning – Differences introduced by prior familiarity with the place - Jaalama Kaisa; Fagerholm Nora; Julin Arttu; Virtanen Juho-Pekka; Maksimainen Mikko; Hyyppä Hannu (Elsevier B.V., 2022)
Technological development towards increased visual quality and accessibility has made photorealistic 3D geovisualizations an interesting tool for communication in urban planning. Particularly the ability to support perception is important in assessing 3D geovisualizations’ effectiveness for communication. We applied both the concept of sense of presence, i.e. effectiveness of the medium, and sense of place, i.e. meanings and affordances, in a user study conducted through a web-based 3D geovisualization. The study addressed a shopping mall in Helsinki, Finland. We collected a sample of adolescent respondents (n = 122), both familiar and unfamiliar with the geovisualized place in question. Adolescents responded to a survey addressing their perceptions of the mall after the virtual visit. The results indicate that prior familiarity with the place affects the results with the sense of presence, sense of place and preferred urban planning outcome. Familiar respondents were more likely to prefer preservation of the mall. The results show how sense of presence and sense of place work in interplay in the perception of a photorealistic 3D geovisualization. Perception is not only dependent on the realism the 3D geovisualization is able to transmit but also on the individual knowledge and experiences of the audience. According to the results, 3D geovisualizations are best used as supportive tools in communication for urban planning and secondary to a real visit.